Marketer as a Barbie Game Changer - Widyani, Donafeby; Joseph Chen (Publisher Cv. Inara, 2021)
This paper addresses issues about how the Barbie doll can provide an unrealistic vision of how women should look and what marketers can do about it. Barbie is a well-known doll that has become a role model for girls. However, Barbie dolls have attracted much criticism. Studies found that Barbie shapes the body image of young girls and possibly creates body dissatisfaction and low self-esteem among girls. Body dissatisfaction can lead to eating disorders and low self-esteem can lead to depressive behavior. Answering that phenomenon, Barbie launched Barbie Fashionista that has a diverse body type. However, Girls still tend to choose thinner Barbie. Barbie’s marketer should encourage girls to play more with a more realistic body image Barbie such as curvy, tall, and petite, and encourage the children to feel good about their bodies.